Overexpression of meloe gene in melanomas is controlled both by specific transcription factors and hypomethylation. - Mathilde Bobinet; Virginie Vignard; Laetitia Florenceau; Francois Lang; Nathalie Labarriere; Agnès Moreau-Aubry (PLoS ONE, 2013)
The melanoma antigens MELOE-1 and MELOE-2 are encoded by a messenger, called meloe, overexpressed in melanomas compared with other tumour cell types and healthy tissues. They are both able to elicit melanoma-specific T cell responses in melanoma patients, and MELOE-1-specific CD8 T cells have been involved in melanoma immunosurveillance. With the aim to develop immunotherapies targeting this antigen, we investigated the transcriptional mechanisms leading to the preferential expression of meloe messenger in the melanocytic lineage. We defined the minimal promoter region of meloe gene and identified binding motifs for a set of transcription factors. Using mutagenesis, co-transfection experiments and chromatin immunoprecipitation, we showed that transcription factors involved in meloe promoter activity in melanomas were the melanocytic specific SOX9 and SOX10 proteins together with the activated P-CREB protein. Furthermore, we showed that meloe promoter was hypomethylated in melanomas and melanocytes, and hypermethylated in colon cancer cell lines and mesotheliomas, thus explaining the absence of P-CREB binding in these cell lines. This was a second key to explain the overerexpression of meloe messenger in the melanocytic lineage. To our knowledge, such a dual transcriptional control conferring tissue-specificity has never been described for the expression of tumour antigens.